2015
DOI: 10.1002/mabi.201500130
|View full text |Cite
|
Sign up to set email alerts
|

Design, Degradation Mechanism and Long‐Term Cytotoxicity of Poly(l‐lactide) and Poly(Lactide‐co‐ϵ‐Caprolactone) Terpolymer Film and Air‐Spun Nanofiber Scaffold

Abstract: Degradable nanofiber scaffold is known to provide a suitable, versatile and temporary structure for tissue regeneration. However, synthetic nanofiber scaffold must be properly designed to display appropriate tissue response during the degradation process. In this context, this publication focuses on the design of a finely-tuned poly(lactide-co-ϵ-caprolactone) terpolymer (PLCL) that may be appropriate for vascular biomaterials applications and its comparison with well-known semi-crystalline poly(l-lactide) (PLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 70 publications
(125 reference statements)
1
12
0
Order By: Relevance
“…However, our study agrees with several reports demonstrating that, after PLA implantation, there is a mild tissue inflammatory response due to degradation of the polymeric phase, considering that this polymer as biocompatible . Moreover, several reports indicate that the rate of biodegradability of synthetic polymers that degrade over time depends mainly on the intrinsic properties of the polymer, including chemical structure, the presence of hydrolytically unstable bonds, the crystalline‐amorphous ratio, the copolymer ratio level, if applicable, and the initial molecular weight, that it is influenced by physical factors such as the total porosity, pore size distribution, fiber diameter, and chemical factors including the presence of enzymes and the pH at the site of implantation . This aspect could be important because PLA membrane scaffolds synthesized by AJT were amorphous and the in vitro and in vivo degradability could be influenced by the fiber diameter reflected on the mechanical properties indicating changes in the scaffolds properties.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, our study agrees with several reports demonstrating that, after PLA implantation, there is a mild tissue inflammatory response due to degradation of the polymeric phase, considering that this polymer as biocompatible . Moreover, several reports indicate that the rate of biodegradability of synthetic polymers that degrade over time depends mainly on the intrinsic properties of the polymer, including chemical structure, the presence of hydrolytically unstable bonds, the crystalline‐amorphous ratio, the copolymer ratio level, if applicable, and the initial molecular weight, that it is influenced by physical factors such as the total porosity, pore size distribution, fiber diameter, and chemical factors including the presence of enzymes and the pH at the site of implantation . This aspect could be important because PLA membrane scaffolds synthesized by AJT were amorphous and the in vitro and in vivo degradability could be influenced by the fiber diameter reflected on the mechanical properties indicating changes in the scaffolds properties.…”
Section: Discussionsupporting
confidence: 91%
“…[51][52][53] Moreover, several reports indicate that the rate of biodegradability of synthetic polymers that degrade over time depends mainly on the intrinsic properties of the polymer, including chemical structure, the presence of hydrolytically unstable bonds, the crystalline-amorphous ratio, the copolymer ratio level, if applicable, and the initial molecular weight, that it is influenced by physical factors such as the total porosity, pore size distribution, fiber diameter, and chemical factors including the presence of enzymes and the pH at the site of implantation. 24,35,45,46,54,55 This aspect could be important because PLA membrane scaffolds synthesized by AJT were amorphous and the in vitro and in vivo degradability could be influenced by the fiber diameter reflected on the mechanical properties indicating changes in the scaffolds properties. However, the scaffolds exhibited dimensional stability during the degradation period time, which is an important prerequisite for materials evaluation for tissue engineering regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous studies have shown that PLLA materials tend to degrade in an aqueous medium from days 4 to 7, and degradation can lead to a decrease in pH and the release of by‐products to the cell culture medium. These effects, in turn, may have a negative impact on cell physiology and metabolism (Sabbatier et al , ). Although further work should be carried out to test this hypothesis, we suggest that cells cultured in microsphere systems may be initially devoid of these by‐products until they accumulate at day 7 of culture and affect cell proliferation, as determined by PCNA and DMP1 synthesis, thereby also affecting the in vivo degradation rate of S‐BIM.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been implemented to improve the properties of PLA, whilst maintaining its sustainability, including: composite fabrication, 15,16 stereocomplexation, [17][18][19] copolymerization 1,20 and blending. 21,22 While copolymers with P2HEB are rare, 14 PLA copolymers are now commonplace, with glycolide and ethylene glycol copolymers being the most commercially relevant.…”
Section: Introductionmentioning
confidence: 99%